PkM Pengolahan Produk Susu dengan Pendekatan Asset-Based Community Development (ABCD) di Kawasan Penghasil Susu Boyolali Jawa Tengah - Nurwulan Purnasari; Ahmadi Fathurrohman Dardiri; Joko Roby Prasetiyo (Universitas Nurul Jadid, 2023)
Dairy products are essential in supplying the human body's need for animal protein. However, paying attention to the manufacturing process, which not only has to be sustainable but may also drive the economy of the grassroots community, is equally crucial. The purpose of this article is to provide an overview of the community service activities we carried out in Kebonijo, a village in Boyolali district, and in particular the Ngudi Santoso Livestock Farmer Group. Our team was successful in conducting an inventory of community assets, which included physical, human, social, and natural assets, using the ABCD (Asset Based Community Development) approach. The results of the activities show that these activities are needed by the community and are compatible with the assets that the community already owns. ABCD-based activities are intended to increase future national economic resilience while also empowering the community's potential assets.